Programmes & praxis: a review of taken-for-granted knowledge - Leon Fulcher (Scottish Journal of Residential Child Care)
Over the past decade, the term programme has entered the daily language of residential child and youth care workers, managers and planners in Scotland, almost as though it has always described a schedule of activities and routines operating in and around group care services. This term has been used extensively in North America since the end of the Second World War but was much less common in the United Kingdom until recent years. References to programme vary, ranging from personalised care & treatment programmes or curricula, as with the components of an anger-management programme, to directed-learning opportunities using programmed instruction or a schedule of service outputs supplied through purchase of service agreements with government.